2020
DOI: 10.20471/acc.2020.59.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin Correlates with Serum Adipokines in Normal Weight and Overweight Asymptomatic Adults

Abstract: Overweight and obesity are considered as chronic low-grade inflammation accompanied by imbalanced production of adipokines. The aim of this study was to elucidate the relationship between serum bilirubin, which is an endogenous antioxidant with anti-inflammatory activity, and pro-and anti-inflammatory serum adipokines in asymptomatic normal weight and overweight individuals. Healthy men and women aged 25-49 participated in this cross-sectional study. All participants underwent fasting serological measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…We also found that Mttp levels were low in Ppara HepKO mice, suggesting that Mttp is regulated via PPARα (Stec et al, 2019). Previous studies have shown a negative correlation between serum total bilirubin levels and blood triglyceride levels (Zhong et al, 2017;Petelin et al, 2020). Interestingly, in obese patients with low serum total bilirubin and higher triglycerides than lean control with bariatric surgery increased plasma bilirubin by two-fold and reduced triglycerides by 50% (Bawahab et al, 2017), illustrating the potential role of bilirubin in triglyceride metabolism.…”
Section: Discussionsupporting
confidence: 65%
“…We also found that Mttp levels were low in Ppara HepKO mice, suggesting that Mttp is regulated via PPARα (Stec et al, 2019). Previous studies have shown a negative correlation between serum total bilirubin levels and blood triglyceride levels (Zhong et al, 2017;Petelin et al, 2020). Interestingly, in obese patients with low serum total bilirubin and higher triglycerides than lean control with bariatric surgery increased plasma bilirubin by two-fold and reduced triglycerides by 50% (Bawahab et al, 2017), illustrating the potential role of bilirubin in triglyceride metabolism.…”
Section: Discussionsupporting
confidence: 65%
“…Chronic overfeeding induces adipocyte hypertrophy, and then activates inflammatory pathways and accelerates inflammatory cells’ infiltration in adipose tissue, which further promote chronic low-grade inflammation and systemic insulin resistance in diet-induced obese mice ( 15 17 ). A recent human study showed that serum bilirubin level was negatively associated with inflammatory cytokines such as TNF-α, IL-6 and CRP, and positively associated with anti-inflammatory adiponectin ( 18 ). Consistently, our study showed that relatively reduced inflammatory state and heightened insulin sensitivity predicted favorable metabolic parameters in MHO patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, we found that the proinflammatory effect of GGT may be through the promotion of IL-6 levels, which leads to CRP levels rise, consumption of more complement, making the increase of GGT become a risk factor for SLE aggravation (28,29). At the same time, we also found that the anti-inflammatory effect of TBIL may be reflected by inhibiting TNF-a levels, which leads to the decrease of CRP level and decrease of complement consumption, making the decrease of TBIL a risk factor for SLE aggravation (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 69%